Fiscal policy and economic cycle in northern entities of Mexico - Ramirez Rodríguez , Roberto (Posgrados de la División de Ciencias Económica Administrativas, 2022)
The objective of this articul is to carry out a historical review of the main studies that have been carried out to quantify the impulse or impact of fiscal policy on economic activity. Also, apply the budget impulse technique to measure both the marginal contribution of the budget in global demand. As well as the cyclical impulse, be it neutral, expansive or depressive on economic activity, for seven states in northern Mexico. Finally, the results of the fiscal impulse policy in the behavior of the economic cycle are interpreted from annual time series and quarterly time series in the seven northern states of Mexico, in the main phases of the economic cycle. To effect, to demonstrate whether or not procyclical or countercyclical state fiscal policies are applied in the different phases of the economic cycle, paying special attention to the contractionary phases of economic activity.